Constitutional Law and the Dismissal of Indonesia’s President and Vice President: Accountability and Democratic Resilience - Mohd. Yasin; Nurul Hidayah Tumadi; Mumtaz Mumtaz; Fathurrahman Fathurrahman; Robin Fernando Putra (JURNAL AKTA, 2026)
This study explores the constitutional processes surrounding the dismissal of the President and Vice President in Indonesia, focusing on legal mechanisms, government accountability, and the impact on democratic resilience. Using a qualitative approach with a literature review and library research, this study examines relevant legal frameworks, political dynamics, and institutional roles in the impeachment process. The findings reveal that while Indonesia’s Constitution provides clear guidelines for presidential dismissal, ambiguities in the criteria for “grave violations” and the potential for political manipulation of the process pose significant challenges. Furthermore, the research highlights that while the impeachment process can reinforce government accountability, its politicization can undermine public trust and destabilize democratic institutions. The study concludes that strengthening the independence of key institutions, such as the Constitutional Court and the People’s Consultative Assembly, is crucial to preserving democratic integrity and ensuring the legitimacy of the impeachment process. This work contributes to the ongoing discourse on constitutional law and democratic governance in Indonesia and provides recommendations for future legal and institutional reforms.